Bayesian model and selection signature analyses reveal risk factors for canine atopic dermatitis - Katarina Tengvall; Elisabeth Sundström; Chao Wang; Kerstin Bergvall; Ola Wallerman; Eric Pederson; Åsa Karlsson; Naomi D. Harvey; Sarah C. Blott; Natasha Olby; Thierry Olivry; Gustaf Brander; et al. (Communications Biology, 2022)
A genome-wide evaluation in four different dog breeds identifies multiple genomic regions that were significantly related to risk of atopic dermatitis, providing additional biological insights into disease pathogenesis in dogs.